NS MATRIX AS A MARKET RESEARCH ANALYSIS METHOD: MAKING DECISIONS ON PRODUCT POSITIONING - Viktor Nikolenko; Svitlana Ivanova (Економіка та суспільство)
Market research plays a crucial role in the success of businesses, whether large or small. It provides valuable insights into customer preferences, market dynamics, and competitive forces. By thoroughly understanding the behaviors and demands of their target audience, businesses can make informed decisions that enhance product offerings, optimize marketing strategies, and reduce risks. This research evaluates the strengths and limitations of traditional market analysis models while introducing the innovative NS Matrix model, aimed at simplifying and enhancing market research processes for companies of all sizes. The goal is to offer businesses a more efficient, accessible, and comprehensive approach to analyzing market trends and consumer behavior, ultimately supporting strategic decision-making and business growth in an increasingly competitive environment.